Farmers’ Perceptions towards Marketing Problems and Challenges in Floriculture in Solan District of Himachal Pradesh, India - Kumari, Manisha; Mehta, Piyush; Raina, Krishan Kumar (International Journal of Economic Plants, 2016)
Study was conducted on Farmers’ Perceptions towards Marketing Problems and Challenges in Floriculture in Solan District of Himachal Pradesh. The key objectives of the study were to understand the marketing activities undertaken by floriculture growers trace out the key marketing problems faced by the farmers in floriculture and seek farmers’ opinion to meet marketing challenges in floriculture business. For this paper, sample size of 60 farmers of Solan block of Himachal Pradesh was taken. Transportation was considered with highest awareness among florists, on account of its focal basis on the sustenance of floriculture business. Research study highlighted various marketing problems, like lack of market awareness, lack of transportation and storage facilities faced by the florists emerging as the greatest hurdle in the floriculture. The study highlighted that there is an urgent need of improving the awareness level regarding the floriculture business. And higher marketing efficiency and better returns to producers through direct retailing is a clear indicator for developing farmer’s markets in the region.